"Abusive Furniture": Visual Metonymy and the Hungarian Stop Violence Against Women Campaign. Issue 4 (2nd October 2017) - Goehring, Charles; Renegar, Valerie; Puhl, Laura
ABSTRACT: In this essay, we argue that Amnesty international's media campaign against domestic violence unwittingly directs attention away from perpetrators of abuse to their victims. This reinforcement happens through the visual features of the campaign and, more specifically, through metonymic substitution. We examine three imagetexts from an Amnesty International media campaign in Hungary targeting domestic violence to better understand the function and implication of visual metonymy. Each imagetext features a woman next to a household object that metonymically replaces a perpetrator of domestic abuse. Using vector analysis, we suggest that compositional factors and text in each imagetext work together to focus attention on specific aspects of the image. In these imagetexts, metonymic substitution functions to hide the perpetrators of violence and instead focus attention on the victims for making excuses about their own victimization.